DARD, Olivier & Ana Isabel Sardinha-Desvignes. 2018. Célébrer Salazar en France (1930-1974): Du philosalazarisme au salazarisme français. Bruxelles : Peter Lang (Convergences, vol. 90). - Almeida, Dimitri (apropos [Perspektiven auf die Romania], 2020)
Rezension